Tropical forest soil characteristics in rehabilitated forests of Malaysia - Karam, Daljit Singh; Abdu, Arifin; Sundara Rajoo, Keeren; Jamaluddin, Aiza Shaliha; Karim, Md. Rezaul (Universiti Putra Malaysia Press, 2017)
The coordinated efforts of rehabilitating forests, either for its natural resources or for environmental reasons, has always been a priority especially in tropical regions that experience high levels of weathering. This book summarizes significant studies on soil properties of selected forest reserves and cultivated lands around Malaysia. The research on forest soils covered in these studies are largely on the forest reserves of Chikus, Tapah Hill and Kinta forest in Perak, Malaysia. Some soil properties evaluation was also carried out in different land usage areas in Bintulu, Sarawak. The last chapter is on research about using valuable tropical forest trees to remediate contaminated forest soil through phytoremediation. The book comprises of extensive information on the interpretation of results of soil analyses; the interpretation is done in a simple and easy to understand manner. This book is ideal for any student, researcher or member of the public that wants to know more about the nature of forest soils.